Spectrophotometric Determination of Mercury (ІІ) With Michler’sthioketon Reagent - Alaa Frak Hussain (Journal of Global Pharma Technology, 2019)
A new simple, rapid and sensitive spectrophotometric method has been develop to determine mercury (ІІ) ions by using Michlerۥs thioketone reagent (Ligand) to formed a dark blue complex at ( pH=7), The complex was found to be with stability for(120 min)at the given pH , The complex formed in this method give obeys Beer’s law over the concentration  range (1.473x10-5 M–10.313x10-5M) with a detection limit of (5.235x10 -7 M)and molar absorptivity (0.339x104 L mol-1cm-1) ,The Stoichiometry of the complex was confirmed by using(Mole Ratio method &Molard method) the two methods using indicated the ratio of reagent to metal is 1:1,The effect of the presence of different cations and anions as interference in the determination of mercury (ІІ) under the given condition were investigated, The mercury complex formed has been characterize by UV- visible ray , Precision and accuracy of the new method has been study by terms of  Relative standard deviations  (RSD%), and analytical error.Keywords: Michler’sthioketon Reagent, Stoichometry, Absorptivity.